Private Universities in a Public Framework: The Italian Experience - Hunter, Fiona (International Higher Education, 2010)
Private higher education has been in the periphery in western Europe. In Italy, since the 20th century, nonstate - private sector of higher education has expanded because of financial pressure on the state higher education budget. Private universities are largely governed by the national regulatory framework since they are self-funded mostly from tuition, but also receive small contributions from the state budget. They have less financial accountability than public institutions. Reputation varies at each institution. Despite the recent significant expansion, and a of private sector remains peripheral.